OTUB1 is a key regulator of RIG-I-dependent immune signaling and is targeted for proteasomal degradation by influenza A NS1 - Jahan, AS; Biquand, E; Muñoz-Moreno, R; Le Quang, A; Mok, CK-P; Wong, HH; Teo, QW; Valkenburg, SA; Chin, AWH; Man Poon, LL; Te Velthuis, A; García-Sastre, A; et al. (Elsevier, 2020)
Deubiquitylases (DUBs) regulate critical signaling pathways at the intersection of host immunity and viral pathogenesis. Although RIG-I activation is heavily dependent on ubiquitylation, systematic analyses of DUBs that regulate this pathway have not been performed. Using a ubiquitin C-terminal electrophile, we profile DUBs that function during influenza A virus (IAV) infection and isolate OTUB1 as a key regulator of RIG-I-dependent antiviral responses. Upon infection, OTUB1 relocalizes from the nucleus to mitochondrial membranes together with RIG-I, viral PB2, and NS1. Its expression depends on competing effects of interferon stimulation and IAV-triggered degradation. OTUB1 activates RIG-I via a dual mechanism of K48 polyubiquitin hydrolysis and formation of an E2-repressive complex with UBCH5c. We reconstitute this mechanism in a cell-free system comprising [35S]IRF3, purified RIG-I, mitochondrial membranes, and cytosol expressing OTUB1 variants. A range of IAV NS1 proteins trigger proteasomal degradation of OTUB1, antagonizing the RIG-I signaling cascade and antiviral responses.